PENGGUNAAN INTERNET DI KALANGAN PETANI SAYUR DALAM MEMPEROLEH INFORMASI PERTANIAN DI KABUPATEN CIANJUR - Ali Alamsyah Kusumadinata (Fakultas Pertanian, Universitas Riau, 2016)
The Internet is one of the information is open and easily accessible. Internet usage continues to rise with the increasing use of technology. Farmers is one of the users who have the benefit of the Internet media. This study aims to (1) describe the use of the internet among farmers, (2) analyzing internet use among farmers. This study uses a case study approach case approach that uses quantitative and qualitative data. The data are drawn from these cases are farmers Cianjur Cipanas village with vegetable commodities. The results of this study showed the majority of farmers use the internet only as part of the entertainment rather than as part of a reliable media information. In addition, use of the Internet is done using mobile applications as compared with opening the computer. This is due to limited capacity and ownership of farmers in accessing the computer. As for suggestions that could be recommended is the need to improve knowledge among farmers with group-based approach.